Upaya Meningkatan Publisitas Melalui Model Integrated Marketing Comunication Pada Sebuah Rumah Sakit Swasta di Tangerang Selatan - Surti Wardani; Arif Siaha Widodo (Jurnal Pemasaran Kompetitif, 2020)
There are two Hermina Hospitals in South Tangerang. Although they have implemented a marketing communication strategy but not the Integrated Marketing Communication (IMC) model. This research aims to describe the marketing communication strategy used by the Hermina Hospital in South Tengerang. The focus of this research is on how marketing communication is available at the two Hermina Hospitals in making marketing communication models so that the services delivered are integrated. The method of this research is descriptive qualitative by observing the public. Data obtained by interviewing informants. The selection of research informants was by using purposive sampling method to obtain information about tyhe characteristics of the hospital service user community. The results of the study produced an integrated marketing communication model can be used as a basis for making policies in increasing hospital publicity.Keywords: Strategy, Model, Integrated Marketing Communication (IMC).